Macroquality measurement: world state of quality and European quality scoreboard approaches and results. (3rd July 2020) - Saraiva, Pedro; Sampaio, Paulo; Cubo, Catarina; Reis, Marco
Abstract : Quality can be analyzed according to several dimensions. In particular, it can and should be more and more considered under the scope of a multiscale view, encompassing different orders of magnitude both in time and space. In a globalised world, it is also important to compare quality performances across organisations, but also territories and countries, within the scales of time and space of what one may designate as 'macroquality'. A lack of compiled information, data analysis efforts or methodologies were found regarding the characterisation of the World State of Quality, or the establishment of country rankings and comparisons. As a result of this gap and the relevance of its scope, we decided to conduct a research project, presented in this paper, based upon a framework that aims to understand, measure and compare macroquality performances achieved by different countries, in the frame of an underlying model that comprises a total of 10 dimensions and 21 indicators. The first results obtained correspond to the 28 European Union countries (European Quality Scoreboard). Following this approach, strengths, weaknesses, priorities and areas for improvement can also be identified, and new strategies or policies defined taking into account the performances obtained.